ANALISA HIDROLOGI DAN HIDROLIKA PADA DAERAH ALIRAN SUNGAI (DAS) KALI PACAL BOJONEGORO - Harjono, Harjono; Widhiastuti, Yulis (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2019)
Erosion and sedimentation are two interrelated problems. In the Pacal river catchment area, in its development there has been environmental damage which has caused problems in watershed management in the form of changes in the function of paddy fields which basically results in a decline in the amount of water demand. The aim of the study was to monitor and evaluate the performance of the Pacal River sub-watershed using water management criteria. The results of the study found that the Flood calculation for 5 years with the Harpes method with Debit yields of 443,678 m³ / sec, the Rational method produced 413,495 m³ / sec and the Melchoir method produced 412,824 m³ / sec.